Spatial Dynamics And Risks Analysis Of Lowlands Degradation Potential Around Of Nakanbé-Dem Sub-Watershed In Center-Nord Of Burkina Faso (West Africa): Through Multi-Date Study And Satellite Tele-Analysis - Adama Ilboudo; Sâga Sawadogo; Soungalo Soulama; Edmond Hien; Zombre Prosper (European Scientific Journal, ESJ, 2020)
Watershed degradation is a key issue for environmental change in the Sahel region and causes an unprecedented threat to the lowlands watershed and the livelihood of local people. This study analyzes the spatial dynamics and degradation risks of Nakanbé-Dem sub-watershed lowlands’potential. The study combines lowlands plants species assessment and digital processing. Lowlands spatio-temporal dynamics were assayed from landsat images of 1986, 1996, 2006 and 2016. Vegetation data and soil physical and chemical parameters allowed to characterize lowlands degradation states. Lowlands degradation risk assessment is based on flora analysis and remote sensing indices (Normalized Difference Vegetation Index, Normalized Difference Water Index, slope values and water accumulation zones). Spatio-temporal dynamics analysis between 1986 and 2016 showed a continuous degradation of Nakanbé-Dem lowlands potential. The coverage of farming land increased from 31 to 51% compared to the total lowland potential of 43320 ha. The riparian formations have decreased by 4.11% in the same period. As concerns the lowland beds, their coverage rate has continuously decreased from 24% in 1986 to 7.79% in 2016. The coverage rate of water bodies has not kept a linear evolution. It went from 2.27 to 2.62%, a slight increase of 0.35%. Soil and flora samples were taken from the three lowland geomorphological subunits: glacis, hillside and the central zone. Soil analyze concerned the following parameters: useful watercontent, saturation rate, carbon, nitrogen, potassium and bulk density. Flora parameters analyzed are: woody cover, density of regeneration individuals, tree density, quadratic diameter, tree height, ligneous plants species richness, herbaceous species richness. These different measurements have been taken on the glacis, hillside and central zone. Flora and soils analysis showed difference in lowlands topographic structures. Unlike hillside and glacis, their central zone is less degraded. It is characterized by an average specific richness of woody plants about 3.43% against 3.13 % for hillsides and 2. 44 % for glacis. Tree average density (129.29 in/ha), the number of trees large diameter (118. 55 in/ha) and woody cover (61.79 %) are higher in the central zone than on the hillsides and glacis. From Pedological aspects, central zone is characterized by a concentration great of organic matter (1.49%) (great rate of carbon and nitrogen) against 0.89 for glacis and 0.90 for hillsides. The useful water content (19.75 %) and the saturation rate (64.85) in the central zone are great. These values are low on the glacis (9.36 and 63,77) and hillsides (12.17 and 59.66).In the current context of persistent climatic pressure, the conquering of new farms will accelerate the growth of cropped acreages and increase the degradation risk of lowlands’ potential. Lowlands’ dynamic apprehension can serve as a basis of development and endogenous programs implementation to restore sub-watershed lowland’ potential.